Nanophotonic Polarization Routers Based on an Intelligent Algorithm. Issue 10 (23rd February 2020) - Lu, Cuicui; Liu, Zhouhui; Wu, You; Xiao, Zhiyuan; Yu, Dongyi; Zhang, Hongyu; Wang, Chenyang; Hu, Xiaoyong; Liu, Yong‐Chun; Liu, Xiaohong; Zhang, Xiangdong
Abstract: Nanophotonic polarization routers, which can separate and steer light with different polarizations of transverse electric and transverse magnetic modes into different output ports, are an essential component of on‐chip integrated photonic circuits. By developing an intelligent algorithm that combines the genetic algorithm and the finite element method, various polarization routers possessing different operation bands, different structures, and different materials, which can be easily fabricated and integrated, are successfully designed. On‐chip ultrasmall silicon‐based polarization routers are experimentally demonstrated in the near‐infrared range. The footprint is only 970 nm × 1240 nm, which is the smallest demonstrated. The measured normalized transmission is up to 85% in the near infrared range. Additionally, a broadband highly efficient photon coupler is also achieved based on disordered‐grating configurations designed by the intelligent algorithm. This breaks the restrictions of traditional structures, provides a universal platform for the realization of nanophotonic polarization routers, and paves a way for the design and high‐density on‐chip integration of nanophotonic devices. Abstract : A polarization router can separate and steer light with different polarizations into different output ports. A silicon‐based polarization router with a footprint of 970 nm × 1240 nm is realized based on an intelligent algorithm, which is the smallest demonstrated experimentally. Additionally, various polarization routers exhibiting different operation bands, structures and materials are designed by this intelligent algorithm.